Acoustic Emission Analysis of the Cracking Behavior in ECC-LWSCC Composites - Yara Zaki; Ahmed Abouhussien; Assem Hassan (Applied Sciences)
Acoustic emission (AE) analysis was utilized to assess the cracking behavior of six lightweight self-consolidating concrete (LWSCC)–engineering cementitious composite (ECC) beams under flexural loading. Two control beams were fully cast with ECC containing either polyvinyl alcohol (PVA) fibers or steel fibers (SF). The remaining four beams were ECC-LWSCC composite beams, with the ECC layer containing PVA fibers or SF placed on either the tension or compression side. The results showed that the control beams had the highest ultimate load capacity, followed by beams repaired in tension, and then beams repaired in compression. PVA fibers exhibited higher performance compared to steel fibers at the first crack load, while steel fibers enhanced the beam’s performance at the ultimate load stage. During the flexural testing, AE parameters such as the number of hits, signal amplitude, and cumulative signal strength (CSS) were collected until failure. The analysis of these AE parameters was effective in detecting the first crack and evaluating cracking propagation in all beams. Changing the type of fibers (PVA and SF) in the ECC layer showed a significant effect on AE parameters. Moreover, adding a new ECC layer to an existing LWSCC layer resulted in variations in the signal amplitude. Finally, the flexural failure mode was confirmed with the aid of the rise time/maximum amplitude vs. average frequency analysis.